The Linguistic Effects of Peer Editing as a Technique in Improving Collegiate Compositions - Myla Santos (Indonesian Research Journal in Education |IRJE|, 2021)
This study aimed to analyze the linguistic effects of peer editing in improving student’s composition.  Specifically, it described the revision priorities, types and extent of revision in peer editing. 50 students from two sections of Teacher Education programs at the College of Education, Central Luzon State University were randomly selected as participants. Descriptive - inferential research method was used. Results show that nouns and verbs were edited the most, and frequent revisions were substitution and deletion, and distribution and addition for first draft and second draft respectively. Data also show the employed functions of revision were grammatical and explicature, and the size of revision was at sentence level. T-test  results show that peer editing was highly significant in over-all quality and in number of words. Because of the freer atmosphere of peer editing, students were not inhibited by the impositions of corrections, hence they developed empowerment and self-efficacy.